Integrating Technology into Mathematics Teaching - Incikabi, Lutfi; Tokmak, Hatice Sancar (IGI Global, 2013)
The relationships between content, pedagogy, and technology are important for teaching, yet complex for teachers. The idea of technological, pedagogical, and content knowledge (TPACK) has emerged in the educational technology field as a framework to explain the complexity of technology integration. In contrast to a simple view of technology, TPACK framework emphasizes the connections, interactions, affordances, and constraints of content, pedagogy, and technology. TPACK framework presents a way of thinking about effective technology integration. The preparation of teachers for effective technology integration to instruction appears to be a key component of almost every improvement plan for education and educational reform programs. This chapter provides a course design example for teacher educators about how to give pre-service teachers experience integrating technology with their instructions. The instructor designed this course to enhance mathematics teacher candidates’ understanding of TPACK as a result of an intense educational technology course sequence.
Keywords: 9. Industry and infrastructure; 4. Education; 10. No inequality; 12. Responsible consumption